The place of trust in the system of value preferences of students involved in sports - Tatyanina L.G. ,; Yakovleva Y.A. ,; Alekseeva N.D. ,; Rogalev A.S. , (Theory and Practice of Physical Culture, 2025)
Objective of the study is to study the role of trust in the value system of students who actively engage in sports. Methods and structure of the study. The empirical study involved 128 students (aged 18-22) enrolled in 2-4 courses at various universities in St. Petersburg.: LSU named after A.S. Pushkin, NSU named after P.F. Lesgaft, St. Petersburg Mining University of Empress Catherine II and BSTU "VOENMEH" named after D.F. Ustinov. All participants are active athletes with sports qualifications from the first category to the Master of sports. To achieve the purpose of the study, a set of psychodiagnostic tools was used: the questionnaire "Trust" (developed by L.G. Pochebut and co-authors), the methodology of Sh. Schwartz's test for the study of values, as well as the test of D.A. Leontiev "Meaningful life orientations" (SSO). The article presents the results of a study conducted to analyze the relationship between trust and value orientations among students who are professionally involved in sports. Results and conclusion. The analysis of the value structure of student-athletes revealed the predominance of values related to the needs of the group, such as safety, observance of norms and traditions, regardless of the level of trust. Students with a high level of trust demonstrate a greater propensity for mutual understanding, positive interaction, and tolerance. Personal achievements, hedonism, and the pursuit of prestige are less important to them. Students with a low level of trust, on the contrary, are more focused on individualistic values, personal needs and show less willingness to cooperate and trust in a team.